VoIP System Implementation Using Issabel as an Integrated IP PBX Server with Telco Vendors - Riefand Fadhlurrohman; Agung Triayudi; Ratih Titi Komala Sari (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2024)
In today's telecommunication world, we cannot be separated from long-distance communication using telephones, either personal needs or mass needs. Therefore, this research aims to introduce a system that may be less familiar today, namely the VoIP System Implementation Using Issabel as an Integrated IP PBX Server with Telco Vendors. In this research, the author conducted experiments using VirtualBox to support thesis writing and using one of the providers that the author borrowed from the office in order to make calls to GSM and PSTN. The author observes that currently there are quite a lot of call centres that need this system to support employee performance and cost efficiency. Through this journal, the author hopes that entrepreneurs or telecommunication companies can gain an understanding of the VoIP System and IP PBX Server to be implemented.